Tindak Pidana Kekerasan Seksual Terhadap Anak (Studi Komparatif Indonesia dan Malaysia) - Rosedila, Shafa; Susanti, Rahtami (Universitas Muhammadiyah Kotabumi, 2024)
This research discusses the crime of sexual violence against children in Indonesia and Malaysia. This research is a normative juridical research using a comparative approach. This research aims to analyze the differences and similarities of the legal frameworks of the two countries, considering that Indonesia adheres to the Civil Law Law system, while Malaysia adopts Common Law. Data shows that in 2024, Indonesia recorded more than 23,000 cases of sexual violence against children, while Malaysia reported nearly 3,000 cases in early 2023. This article highlights challenges in law implementation, the need for policy reform, as well as the importance of adequate psychological support for victims as part of recovery efforts. The research provides recommendations to strengthen child legal protection in both countries, with the hope of promoting more effective responses to child sexual crimes and contributing to the academic literature on this issue.